Application of the STAD Type Cooperative Learning Model Based on Real Experience in Improving Student Learning Outcomes in Science Learning Subjects of Movement in the Movement of Animals and Plants in Junior High Schools - Irsan, Irsan; Jamhari, Mohammad; Bialangi, Mursito (FKIP Universitas Tadulako, 2023)
The research method uses the Hopkins model design which consists of 4 stages, namely planning, implementation, observation and reflection. Data collection techniques using observation and test methods. The results showed that the percentage of student activity in cycle I was 69% (enough), increased in cycle II to 88% (very good), the percentage of teacher activity in cycle I was 72% (enough), increased in cycle II to 91% (very good). Good). Likewise with the assessment of student learning outcomes; the percentage of attitude evaluation in cycle I was 87% increased in cycle II to 90%, evaluation of the realm of knowledge in cycle I for Classical absorption (CA) 74% and Classical Learning Mastery (KKB) 83% increased in cycle II to Classical absorption (CA) 80% and Classical Learning Mastery (PKK) 93%, the assessment of the domain of skills in cycle I was 69% increased in cycle II to 94%. Based on these results it can be concluded that the application of the STAD type cooperative learning model based on real experience can improve the learning outcomes of class VIII students in learning science on the movement of animals and plants at SMP Negeri 1 Tombusabora Sindue.